2019
DOI: 10.1371/journal.pone.0218785
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and social-cognitive abilities in older adults: Convergent evidence from self-report measures and cardiovascular reactivity

Abstract: Recently, some authors have suggested that age-related impairments in social-cognitive abilities—emotion recognition (ER) and theory of mind (ToM)—may be explained in terms of reduced motivation and effort mobilization in older adults. We examined performance on ER and ToM tasks, as well as corresponding control tasks, experimentally manipulating self-involvement. Sixty-one older adults and 57 young adults were randomly assigned to either a High or Low self-involvement condition. In the first condition, self-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In this study, ordinal logistic regression analysis showed that 24‐hour, daytime and nighttime systolic ARV and CV, but not diastolic parameters, were independently associated with frailty. A possible explanation for this may be that sympathetic nervous system is an important regulator of short‐term blood pressure, 45 in particular, systolic blood pressure reflects sympathetic nervous system activation 46 . However, it has been suggested that the sympathetic nervous activity was decreased in older adults with frailty 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ordinal logistic regression analysis showed that 24‐hour, daytime and nighttime systolic ARV and CV, but not diastolic parameters, were independently associated with frailty. A possible explanation for this may be that sympathetic nervous system is an important regulator of short‐term blood pressure, 45 in particular, systolic blood pressure reflects sympathetic nervous system activation 46 . However, it has been suggested that the sympathetic nervous activity was decreased in older adults with frailty 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The review of literature indicates that adult learners tend to show lower levels of engagement in pedagogical activities, as they also cautiously select where to put effort into such activities, and they have their own personal learning goals. Based on these classifications, I argue that independent learners' engagement is overly affected by the perceived importance of the motivational aspect (Ceccato et al, 2019). Kubota (2011) suggests that the learning of a language and the personal and social world of the learner are co-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows how explicitly motivating performance goals increases older adults’ performance. Indeed, age differences in emotion recognition and person perception disappear entirely when people are told that they will need to justify their judgments after completing the task ( Hess et al, 2001 , 2009a , b ; Stanley and Isaacowitz, 2015 ), despite the fact that self-rated motivation does not influence emotion recognition ( Ceccato et al, 2019 ). Thus, evidence of age-related decline in social cognition may be an artifact of older adults’ implicit resource preservation goals which leads to worse performance, especially when there are no consequences for being wrong.…”
Section: “They Will Not”: a Motivation-based Account Of Selective Eng...mentioning
confidence: 99%